Mathematical Methods for Measuring the Visually Enhanced Vestibulo–Ocular Reflex and Preliminary Results from Healthy Subjects and Patient Groups - Rey-Martinez, Jorge; Batuecas-Caletrio, Angel; Matiño, Eusebi; Trinidad-Ruiz, Gabriel; Altuna, Xabier; Perez-Fernandez, Nicolas (Frontiers in Neurology, 2018)
Background: Visually enhanced vestibulo-ocular reflex (VVOR) is a well-known bedside clinical test to evaluate visuo-vestibular interaction, with clinical applications in patients with neurological and vestibular dysfunctions. Owing to recently developed diagnostic technologies, the possibility to perform an easy and objective measurement of the VVOR has increased, but there is a lack of computational methods designed to obtain an objective VVOR measurement. Objectives: To develop a method for the assessment of the VVOR to obtain a gain value that compares head and eye velocities, and to test this method in patients and healthy subjects. Methods: Two computational methods were developed to measure the VVOR test responses: the first method was based on the area under curve of head and eye velocity plots, and the second method was based on the slope of the linear regression obtained for head and eye velocity data. VVOR gain and vestibulo-ocular reflex (VOR) gain were analyzed with the data obtained from 35 subjects divided into 4 groups: healthy (N = 10), unilateral vestibular with vestibular neurectomy (N = 8), bilateral vestibulopathy (N = 12), and CANVAS (N = 5). Results: Intra-class correlation index for the two developed VVOR analysis methods was 0.99. Statistical differences were obtained by ANOVA, comparing the healthy group (VVOR mean gain of 1 ± 0) with all other groups. The CANVAS group exhibited (VVOR mean gain of 0.4 ± 0.1) differences when compared to all other groups. VVOR mean gain for the vestibular bilateral group was 0.8 ± 0.1. VVOR mean gain in the unilateral group was 0.6 ± 0.1, with a Pearson’s correlation of 0.52 obtained when VVOR gain was compared to the VOR gain of the operated side. Conclusion: Two computational methods to measure the gain of VVOR were successfully developed. The VVOR gain values appear to objectively characterize the VVOR alteration observed in CANVAS patients, and also distinguish between healthy subjects and patients with some vestibular disorders.